INVENTARISASI MAKANAN TRADISIONAL JAWA UNSUR SESAJI DI PASAR-PASAR TRADISIONAL KABUPATEN BANTUL - Endang Nurhayati; - Mulyana; Venny Indria Ekowati; Avi Meilawati (Jurnal Penelitian Humaniora, 2014)
This research aims to (1) inventories Javanessee traditional food in Bantul traditional market, (2) describes the name of traditional food as offerings which is related with Javanesee philosophy in Javanessee tradition. It employed the survey technique, it used ethnolinguistic approach. The data sources were collected from 27 traditional markets in Bantul. There were 45 kinds of jajan pasar in traditional market in Bantul region. The food were made from cassava, rice, corn, and lour. The coocking techniques were fried, boiled, steam and roasted. There were food made from peanut and tuber. The food used for offerings were ketan, kolak, apem, jenang, peyek, kacang-kacangan, pala kependhem, jadah, wajik and lemper